What we need to know about PPE associated with the COVID-19 pandemic in the marine environment. (February 2021) - De-la-Torre, Gabriel E.; Aragaw, Tadele Assefa
Abstract: Since the COVID-19 outbreak was declared as a global health emergency, the use of multiple types of plastic-based PPEs as a measure to reduce the infection increased tremendously. Recent evidence suggests that the overuse of PPEs during the COVID-19 pandemic is worsening plastic pollution in the marine environment. In this short focus, we discussed the potential sources, fate, and effects of PPE plastic to the marine environment and proposed five key research needs, involving (1) the occurrence and abundance of PPEs, (2) the sources, fate, and drivers of PPEs, (3) PPEs as a source of microplastics, (4) PPEs as a vector of invasive species and pathogens, and (5) PPEs as a source and vector of chemical pollutants in the marine environment. We suggest that addressing these knowledge gaps will lay the groundwork for improved COVID-19-associated waste management and legislation to prevent marine plastic pollution to continue exacerbating. Graphical abstract: Unlabelled Image Highlights: COVID-19 pandemic has exacerbated plastic pollution worldwide. Evidence suggests that COVID-19 PPEs have reached the marine environment. The abundance and distribution of PPEs need to be addressed. PPE may be a new important source of microplastics in the ocean. Knowledge gaps and research needs have been proposed.